ANALISIS VARIASI TINGKAT KESUBURAN TANAH UNTUK LAHAN SAWAH DI KABUPATEN TANAH DATAR - puja priska cindy; Ratna Wilis (JURNAL BUANA, 2020)
This study aims to determine soil fertility in rice fields in Kabupaten Tanah Datar whose economy is mainly supported by the agricultural sector. This type of research is descriptive by using Fuzzy Set techniques. The results of this study are a map of fertility and suitability of rice paddy fields, which shows a categories suitable for 0,8-1 paddy fields with an area 0f 42.852,60 Ha, class 0,60-0,79 class categories suitable for paddy fields covering 183,99 Ha, and the category does not correspond to the 0,59-0 class for paddy fields with an area of 435,59 Ha. Soil fertility is directly related to plant growth, so an asseeement of soil fertility is absolutelty necessary. The purpose of this study was to determine the level of soil fertility for rice plants in Kabupaten Tanah Datar.